2018
DOI: 10.1063/1.5010417
|View full text |Cite
|
Sign up to set email alerts
|

Formic acid dimers in a nitrogen matrix

Abstract: Formic acid (HCOOH) dimers are studied by infrared spectroscopy in a nitrogen matrix and by ab initio calculations. We benefit from the use of a nitrogen matrix where the lifetime of the higher-energy (cis) conformer is very long (∼11 h vs. 7 min in an argon matrix). As a result, in a nitrogen matrix, a large proportion of the cis conformer can be produced by vibrational excitation of the lower-energy (trans) conformer. Three trans-trans, four trans-cis, and three cis-cis dimers are found in the experiments. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 69 publications
1
12
0
Order By: Relevance
“…Both are of interest for a rigorous comparison between electronic structure theory and experiment. The alternative cooling mechanism by rare gas matrix isolation [16][17][18][19][20][21][22] introduces characteristic matrix embedding shifts on the order of 1-4% for FAD pair modes in Ar 19 , which also complicate the comparison to theory 23,24 .…”
Section: Pair Modes and Their Coupling From Experimental Spectramentioning
confidence: 99%
“…Both are of interest for a rigorous comparison between electronic structure theory and experiment. The alternative cooling mechanism by rare gas matrix isolation [16][17][18][19][20][21][22] introduces characteristic matrix embedding shifts on the order of 1-4% for FAD pair modes in Ar 19 , which also complicate the comparison to theory 23,24 .…”
Section: Pair Modes and Their Coupling From Experimental Spectramentioning
confidence: 99%
“…Recently, Favre et al (2018) reported the first detection of HCOOH towards the TW Hydrae protoplanetatry disk. The observations with the Atacama Large Millimeter/submillimeter Array (ALMA) have shown the trans-HCOOH 6(1,6)-5(1,5) transition at 129 GHz for the lower energy formic acid conformer (Lopes et al 2018), and the measurements revealed a disk-average gas phase trans-HCOOH column density of 2-4 × 10 12 cm −2 , as large as that of methanol CH 3 OH. Cis and trans-HCOOH planar isomer conformers refer to the relative position of the two H atoms in the molecule with respect to C-O bond (Szymafiski & Gillan 1996;Lopes et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The observations with the Atacama Large Millimeter/submillimeter Array (ALMA) have shown the trans-HCOOH 6(1,6)-5(1,5) transition at 129 GHz for the lower energy formic acid conformer (Lopes et al 2018), and the measurements revealed a disk-average gas phase trans-HCOOH column density of 2-4 × 10 12 cm −2 , as large as that of methanol CH 3 OH. Cis and trans-HCOOH planar isomer conformers refer to the relative position of the two H atoms in the molecule with respect to C-O bond (Szymafiski & Gillan 1996;Lopes et al 2018). The radioastronomical observations acquired with the IRAM 30 m telescope revealed the detection of HCOOH even in the comet C/2013R1 (Lovejoy) of planetary system (Makochekanwa et al 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The FA dimer is a prototype for double bonded cyclic complexes; it has been studied extensively [ 5 7 ]. Infrared absorption spectra of FA clusters in noble gas matrices show that FA 3 are chain-like [ 8 ], consistent with its polar character revealed in a molecular beam study utilizing an inhomogeneous electric field [ 9 ].…”
Section: Introductionmentioning
confidence: 99%